2012
DOI: 10.1051/0004-6361/201118112
|View full text |Cite
|
Sign up to set email alerts
|

SN 2009E: a faint clone of SN 1987A

Abstract: Context. 1987A-like events form a rare sub-group of hydrogen-rich core-collapse supernovae that are thought to originate from the explosion of blue supergiant stars. Although SN 1987A is the best known supernova, very few objects of this group have been discovered and, hence, studied. Aims. In this paper we investigate the properties of SN 2009E, which exploded in a relatively nearby spiral galaxy (NGC 4141) and that is probably the faintest 1987A-like supernova discovered so far. We also attempt to character… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
151
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(165 citation statements)
references
References 73 publications
12
151
2
Order By: Relevance
“…Figure 4 shows the maximum likelihood fit of this revised SN 1987A model to the observed SN Refsdal data in all bands (including the optical bands from ACS/WFC). From this fit we find that the color-temperature of SNRefsdal around maximum light is T≈5300 K. This is consistent with the range of temperatures (∼4000-9000 K) seen for other SNe1987A-like events at the same epoch (Pastorello et al 2005(Pastorello et al , 2012Taddia et al 2012). As discussed in Kelly et al (2015a), the SNRefsdal rest-frame optical colors (with B − V ≈ 0.5 mag) are slightly bluer than most SN1987A-like objects.…”
Section: Maximally Constrained Model Fitsupporting
confidence: 88%
See 2 more Smart Citations
“…Figure 4 shows the maximum likelihood fit of this revised SN 1987A model to the observed SN Refsdal data in all bands (including the optical bands from ACS/WFC). From this fit we find that the color-temperature of SNRefsdal around maximum light is T≈5300 K. This is consistent with the range of temperatures (∼4000-9000 K) seen for other SNe1987A-like events at the same epoch (Pastorello et al 2005(Pastorello et al , 2012Taddia et al 2012). As discussed in Kelly et al (2015a), the SNRefsdal rest-frame optical colors (with B − V ≈ 0.5 mag) are slightly bluer than most SN1987A-like objects.…”
Section: Maximally Constrained Model Fitsupporting
confidence: 88%
“…In this case we assume that all bands (F160W, F125W, and F105W) have the same intrinsic light curve shape, meaning that they would reach peak brightness at the same epoch. This is not a good assumption for SN 1987A-like explosions, which tend to reach peak brightness much earlier in bluer bands (e.g., Pastorello et al 2012;Taddia et al 2012). Using both the net posterior probability and the Bayesian Information Criterion (Schwarz 1978) as metrics to evaluate the fitness of these simpler models, we found that we consistently get a better fit when using the more complex alternative.…”
Section: Flexible Curve Fitting Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also the code computes the fallback of material on the central compact object and consequently determines the amount of 56 Ni in the ejected envelope at late times. The code has been widely used to model the observations of core-collapse SNe (e.g., Pastorello et al 2012;Dall'Ora et al 2014;Spiro et al 2014;Takáts et al 2014), having also the capability of simulating the bolometric lightcurve and the time evolution of the photospheric velocity and temperature.…”
Section: Modeling the Post-explosion Evolution Of The Snmentioning
confidence: 99%
“…Two other subclasses have been introduced based on spectral characteristics: IIn for SNe that show narrow H emission lines (Schlegel 1990), and IIb for those that show H in early spectra that soon disappear (Woosley et al 1987). Finally, a few SNe do not fit into the aforementioned subclasses, but show characteristics similar to SN 1987A (e.g., Kleiser et al 2011;Taddia et al 2012;Pastorello et al 2012). More recently, Anderson et al (2014) performed a photometric analysis of a sample of 116 SNe II.…”
Section: Introductionmentioning
confidence: 99%